Interdisciplinaridade na pós-graduação: estudo de seu impacto na produção de teses e dissertações do Programa de Pós-Graduação em História das Ciências e das Técnicas e Epistemologia da Universidade Federal do Rio de Janeiro - Mello, Paula Maria Abrantes Cotta de (2017)
Analyzes of the impact of interdisciplinary teaching in postgraduate student production, using as sampling the thesis and dissertations of the Program of History of Science, Techniques and Epistemology of the Federal University of Rio de Janeiro. Considering the thematic varieties of the disciplines subject and the different academic formation of the teachers, the objective is to identify which areas are most productive in relation to thesis and dissertations, from 2003 to 2014, in order to demonstrate the interdisciplinarity of the Program. For this analysis we used the Goffman Transition Point formula, Bibliometrics methodology, Research area of Information Science, in order to identify words with semantic content among the analyzed material. The results demonstrate the efficiency of the application of the Law presenting a representative picture of the thematic insertion of the areas of knowledge in T & D and show that the great thematic concentration corresponds to the initial areas that gave rise to the Program and the areas incorporated during the analyzed years are still dispersed throughout the production of thesis and dissertations.